2012
DOI: 10.1242/jeb.079186
|View full text |Cite
|
Sign up to set email alerts
|

The energy cost of voluntary running in weasels,Mustela nivalis

Abstract: SUMMARYThe small size and elongate shape of weasels (Mustela nivalis) probably evolved to facilitate movement within the burrow systems of prey species, but result in high energy costs of thermoregulation. In this study we measured metabolic rates of weasels during voluntary locomotion to determine whether energy costs of transport are also high in these unusually shaped mammals. In addition, we measured the lower and upper limits of aerobic metabolism [resting metabolic rate (RMR) and maximal oxygen consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
(100 reference statements)
1
14
0
Order By: Relevance
“…Some researchers have observed higher than expected CoT values in mustelids, such as the least weasel (Mustela nivalis, Fig. 5; Chappell et al, 2013) and the Pacific marten (Martes caurina, Fig. 5; Flaherty et al, 2014), crediting the distinctive morphology of the mustelid form as responsible.…”
Section: Cost Of Transportmentioning
confidence: 86%
See 3 more Smart Citations
“…Some researchers have observed higher than expected CoT values in mustelids, such as the least weasel (Mustela nivalis, Fig. 5; Chappell et al, 2013) and the Pacific marten (Martes caurina, Fig. 5; Flaherty et al, 2014), crediting the distinctive morphology of the mustelid form as responsible.…”
Section: Cost Of Transportmentioning
confidence: 86%
“…These ratios (∼2× RMR for tunnel locomotion; Table 3) are relatively small when compared to such rigorous activities as burrowing (which can be up to 7× RMR; Ebensperger and Bozinovic, 2000b;Luna et al, 2002) or VȮ 2,max which has been reported as 9× RMR in both weasels (Chappell et al, 2013) and mink (Williams, 1983).…”
Section: Degu Kinematics and Energeticsmentioning
confidence: 95%
See 2 more Smart Citations
“…For instance, long-bodied mustelids have a higher surface area to volume ratio that could result in a greater rate of heat loss than mammals of similar body mass (Brown and Lasiewski 1972;Buskirk et al 1988;Harrington et al 2003). It has been hypothesized that to compensate for this increased rate of heat loss, mustelids exhibit greater than expected basal metabolic rate (Iversen 1972;Casey and Casey 1979;Zub et al 2011;Chappell et al 2013), although experimental results are inconclusive (Harrington et al 2003). The reduced limb length, which may decrease drag while swimming (Fish 2000), coupled with the elongated body, likely leads to the higher than expected energetic costs associated with running locomotion previously recorded in mink (Williams 1983) and river otters (Lontra canadensis (Schreber, 1777)) (Williams et al 2002).…”
Section: Introductionmentioning
confidence: 99%